The dynamics of intervention regulation and redistribution in the mixed economy - Kurrild-Klitgaard, Peter (Advances in Austrian economics, 2004)
Since the works by Ludwig von Mises and F.A. von Hayek in the 1920s, the Austrian School of Economics has developed a unique analysis of how the interventions by governments may cause problems, which in turn may lead to calls for further intervention. The Austrian concept of how such a dynamic of interventionism may evolve has however never been very influential outside the Austrian School nor been widely applied for empirical studies. This volume seeks to bring together economists and political scientists with perspectives from both Austrian and public choice analysis so as to further enrich and apply the Mises-Hayek logic, as well as critically assess its value.